Historical Aspects of the Treatment of Cutaneous Leishman - Yu. K. Kuznetsova; V. P. Sergeev; K. Yu. Kuznetsova (Антибиотики и Химиотерапия, 2020)
The article presents historical aspects of the treatment of cutaneous leishmaniasis. The literature data on the treatment of cutaneous leishmaniasis before the 30s of the last century testify to the attempts of chemotherapy of the disease by various means. There were entire groups of means and various treatment regimens in the arsenal of folk healers. This review highlights the treatment of cutaneous leishmaniasis, which existed in the territory of Imperial Russia and the former USSR from ancient times to the present.